Pengaruh Motivasi Intrinsik Dan Kemampuan Terhadap Kepuasan Kerja Pegawai - Dedi Hadian (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2018)
Organizing good governance depends on the readiness of the State apparatus, especially the civil servants. The presence of employees who can provide excellent services leads to this achievement. Besides, the situation can be obtained if the employees have the job satisfaction. When the employees have the high internal motivation and excellent ability in completing their tasks, the job satisfaction can be improved. This study aims to determine the effect of internal motivation and competency on employee job satisfaction in one of the government agencies in West Bandung Regency. The samples were 71 people. The data analysis technique of this research is the path analysis approach. Partially and simultaneously, the intrinsic motivation and competency have a significant effect on employee job satisfaction.